Medical Education in the Abbasid Era: From Mentoring to Qualifying Examinations - Maani, Noor; Almaani, Walid S. (Jordan Medical Journal, 2026)
The Abbasid era heralded a significant epoch marked by remarkable advancements in various scientific disciplines, notably medicine. Successive rulers of this era embarked on a competitive endeavor to leave indelible marks on the progression of both arts and sciences. This paper aims to elucidate the historical trajectory of medical education during this period, elucidating how eminent physicians orchestrated the establishment and management of hospitals while imparting their expertise to aspiring medical practitioners. Much of the foundation of contemporary medical education, encompassing bedside instruction, informed patient consent, resident training incorporating rounds and clinical documentation, culminating in comprehensive qualifying examinations and professional supervision by regulatory entities, can trace its roots back to the Abbasid era.